RESEARCH ON STRESS AND PRECISION CONTROL TECHNOLOGY OF WELDED STEEL PARTS - WEI DongHai; LI KeRui; KUANG Yi; CHENG Peng (Jixie qiangdu)
The residual stress of structural parts of welding machine tools at home and abroad was investigated. The welding bed,column and sliding saddle used in a vertical machining center were manufactured. And the tracking measurement of residual stress and deformation after welding and combined aging treatment were carried out. The results indicated that a large residual stress existed in the structural parts of welding machine tools which was over than 100 MPa. After welded,the maximum initial residual stress of the column,bed and sliding saddle reached 154. 9 MPa,274. 4 MPa and 300. 6 MPa,respectively. The maximum residual stress of the column guide rail,sliding saddle and bed respectively reached 1. 22 mm,2. 24 mm and 2. 88 mm,which approaching or exceeding yield strength of materials so that easily caused large deformation. Through the combined aging treatment of “post-welding-thermal aging-semi-finishing-vibration aging-finishing ”,the stress and deformation of the welding bed,sliding saddle and column are significantly reduced,the maximum residual stress respectively is reduced to 41. 9 MPa,39. 8 MPa and 18. 1 MPa,which all lower than 10%Rm,and the maximum straightness respectively is 36. 69 μm,23. 57μm and 19. 17 μm. After about six months,the deformation of the guide surface is 1 μm/1000 mm ～ 3 μm/1000 mm,which means good accuracy retention. The welding structure can be used for high precision CNC gold cutting machine tools and gear boxes.